Design and Development of Dentistry Ethical Codes: Proposed for National Implementation in Iran - Azam Khorshidian; Bagher Larijani; Mohammad Sadegh Ahmad-Akhoundi; Alireza Parsapour; Abbas Ebadi; Amir Ahmad Shojaei (Tehran University of Medical Sciences, 2019)
Objectives: The dental profession has a special place of trust in the society, and dental clinicians must adhere to ethical standards in all dental procedures. Ethical conduct is one of the main expectations of individuals from this profession. The aim of this study was to design and develop dental ethical codes for national implementation in Iran. Materials and Methods:  This qualitative study was performed using directed content analysis method and purposive sampling. Data were collected until saturation through 15 semi-structured face-to-face individual interviews and two expert panels with academic staffs from dental faculties in Tehran, Iran. Results: Data were classified into five principles and 90 codes. The principles included consideration of patients' interest as a priority, respect for human dignity and patient autonomy, confidentiality of patient information, the excellence of knowledge and skills, and building trust. Conclusion: The ethical codes for Iranian dentists were drafted considering Islamic teachings and the prevailing culture. Some codes were exclusively developed for the cultural atmosphere of Iran especially on topics such as interaction with patients previously treated by other dentists. Some codes addressed the principles of consultation and continuing the therapeutic communication with such patients. Some items have not been considered in codes released by other associations, such as religious considerations in Islamic cover and alcohol consumption that were taken into consideration in this draft. These codes can serve as a guide for professional practice of dentists. It seems that these sets can help us reach the standardized code.